OPERATIONAL COST AND REVENUE IMPACT ON NET PROFIT: PT PERKEBUNAN NUSANTARA IV CASE - Kesia, Tiori; Br. Siringoringo, Magdalena Judika; Dolok Saribu, Ardin (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study examines the impact of operational costs and revenue on net profit at PT Perkebunan Nusantara IV Medan, a key state-owned plantation enterprise in Indonesia. In the face of volatile commodity prices, rising production costs, and increasing competition in the agro-industrial sector, optimizing financial performance has become critical for sustainability. This urgency necessitates a deeper understanding of how cost efficiency and revenue generation jointly influence profitability. Using a quantitative descriptive approach, the research analyzes financial statements from 2019 to 2023, calculating key ratios such as net profit margin and operating cost ratio. Results reveal that sustained profitability is achieved not merely through cost reduction, but through the strategic synergy between disciplined cost control and consistent revenue enhancement. Efficient operational cost management, when aligned with market-driven income growth, significantly boosts net profit. This study highlights the importance of integrated financial strategies in navigating sectoral challenges and ensuring long-term resilience. The findings offer actionable insights for agribusiness managers and policymakers, particularly in emerging economies where state-owned enterprises play a vital role in economic stability. In an era of increasing pressure on agricultural productivity and financial accountability, this research contributes to both theory and practice by emphasizing operational-financial alignment as a lever for sustainable profitability.